Numerical Simulations And Observations of Equatorial F Region Plasma Irregularities - Aveiro, Henrique Carlotto (2012)
This dissertation describes a theoretical, experimental, and modeling investiga- tion of the plasma irregularities in equatorial spread F (ESF). The primary sci- entific objective is to evaluate the electrodynamic nature of equatorial F region plasma instabilities. In particular, the difference between two-dimensional and three-dimensional electrodynamic effects on the onset and evolution of equato- rial instabilities is investigated. Statistical studies are performed using the Jicamarca Unattended Long Term Investigations of the Ionosphere and Atmosphere (JULIA) radar at Jicamarca. The climatology, persistence, and the correlation with the phase of the moon of equatorial spread F irregularities are evaluated, and different forecasting tools are compared. A three dimensional electrostatic numerical model of the equatorial iono- sphere using a finite volume method transport scheme is described. The model incorporates realistic ionospheric conductivities, electric fields, and winds. The model is capable of reproducing the full complement of relevant equatorial F region ionospheric plasma instabilities under realistic conditions, including bot- tomside shear flow. Of chief importance is the so-called “collisional shear insta- bility” which has come to light recently as a potentially important mechanism in the initiation of ESF. This instability has a faster growth rate than the conven- tional generalized Rayleigh Taylor (gRT) instability under typical post-sunset conditions. The combination of gRT and CSI produces an instability which de- velops into an intense ESF event more quickly and with more realistic character- istics than the other two independently in simulations. The model is initialized with data acquired by the C/NOFS satellite, the Jicamarca Radio Observatory, ALTAIR radar, and other ground-based instruments. The forecast potential of the simulation is evaluated through a number of “after the fact” case studies. Various diagnostic codes are used to validate the simulations. To compute the magnetic induction due to ionospheric cur- rents, for example, we solve the partial differencial equation resulting from the Amp` ere’s law for magnetostatics. Airglow emissions corresponding to the sim- ulation runs are likewise computed for the 6300-Å (or oxygen red) line. Simu- lated airglow images are obtained through the integration of the volume emis- sion rates along the camera line of sight. Coherent/incoherent scatter simulations corresponding to the model runs show the typical three stages of ESF evolution, from bottom-type to bottom- side to topside ESF. Some of the features that the simulated electron density maps share with ALTAIR scans include westward tilted ascending depletions connected to the bottomside, periodic spacing of 100-200 km in the zonal di- rection, bifurcation, secondary instabilities growing on the western walls of the primaries, and rates of development. The main goal of these studies has been both to verify the efficacy of the simulation code and its forecast potential while also placing these common but ambiguous diagnostic methods in a formal theoretical/modeling context for the first time.